CONTRIBUTIONS TO THE WORK OF MORAL VALUES IN PHYSICAL EDUCATION FROM TEACHER´S ATTITUDE (Fiep Bulletin - online, 2014)
The aim of this article is to contribute with didactical tools for the practice of moral values in physical education lessons, from a longitudinal approach, which is taking into account all the period of a person's formal education. The article pays attention to the fact that education in values in and through physical education begins in the attitudes and actions that the professor does and does not, assuming that he or she is the main model that the students will follow. That is the reason why, far from suggesting specific activities to work with certain values, the article offers answers about the things that the professor has to take into account to make he's lessons leave a strong mark in values, passing through all the educational levels. The article is structured in two parts: in the first part a definition and theorical approach about values is described. In the second part some didactical tools are offered for the physical education professor to take into account when it comes to give lessons. The article is monographic; it analyses information from multiple bibliographic sources specialized in the topic, complemented with interviews to specialized professionals.
Keywords: values; education; didactical tools